Vibronic coupling in the ground and excited states of the pyridine radical cation - Trofimov, Alexander; Skitnevskaya, A. D.; Grigoricheva, E. K.; Gromov, Evgeniy; Köppel, Horst (The journal of chemical physics, 2020)
Vibronic interactions in the pyridine radical cation ground state, 2A1, and its lowest excited states, 2A2 and 2B1, are studied theoretically. These states originate from the ionization out of the highest occupied orbitals of pyridine, 7a1 (nσ), 1a2 (π), and 2b1 (π), respectively, and give rise to the lowest two photoelectron maxima. According to our previous high-level ab initio calculations [Trofimov et al., J. Chem. Phys. 146, 244307 (2017)], the 2A2 (π−1) excited state is very close in energy to the 2A1 (nσ−1) ground state, which suggests that these states could be vibronically coupled. Our present calculations confirm that this is indeed the case. Moreover, the next higher excited state, 2B1 (π−1), is also involved in the vibronic interaction with the 2A1 (nσ−1) and 2A2 (π−1) states. The three-state vibronic coupling problem was treated within the framework of a linear vibronic coupling model employing parameters derived from the ionization energies of pyridine computed using the linear response coupled-cluster method accounting for single, double, and triple excitations (CC3). The potential energy surfaces of the 2A1 and 2A2 states intersect in the vicinity of the adiabatic minimum of the 2A2 state, while the surfaces of the 2A2 and 2B1 states intersect near the 2B1 state minimum. The spectrum computed using the multi-configuration time-dependent Hartree (MCTDH) method accounting for 24 normal modes is in good qualitative agreement with the experimental spectrum of pyridine obtained using high-resolution He I photoelectron spectroscopy and allows for some assignment of the observed features.